A prospective analysis on drug usage and assessment of health-related quality of life in a medical intensive care unit at a tertiary care teaching hospital - Bhat, Divya S.; Aithal, Sathisha; U. K., Vimarsha (International Journal of Basic & Clinical Pharmacology, 2026)
Background: Drug use research is vital for evaluating prescribing trends and its impact on healthcare. Despite guidelines, intensive care unit (ICU) prescriptions often vary due to patient and prescriber related factors. Analyzing these patterns helps optimize therapy and identify drug related issues. The world health organization (WHO) ATC system enables standardized comparisons but may not reflect actual doses. The EQ-5D-5L questionnaire assesses health related quality of life (HRQoL) and treatment outcomes. This study evaluates of prescription pattern in medical ICU (MICU) and estimates HRQoL index. Methods: A prospective cross-sectional study was conducted in MICU of KVGMCH, Sullia (March to August 2025) after ethical approval (KVGMCIEC202502). Eligible patients were included, excluding those with incomplete data or discharged against medical advice. Data on demographics, diagnosis, ICU stay, drug therapy, treatment outcome, ADRs, HRQoL was collected and descriptively analyzed using excel. Results: Study included 102 patients with 68.62% male and 31.38% of females. Adults (18-64 years) accounted for 64.7%, while elderly (>65 years) were 35.3%. Average drug count was 8.88 per patient, mainly administered intravenously (50.8%) followed by oral (34.9%). ICU stay ranged from 2-8 days on an average and a total of 906 drug were prescribed. Gastrointestinal, respiratory conditions being most common cause of admissions. ceftriaxone-sulbactam was most prescribed drug. Recovery rate was 92.2% and EQ-5D-5L scores improved from -0.923 to 0.897. Conclusions: Analysis of case records revealed that prescribed drugs were despite high antibiotic usage, with improved EQ-5D-5L scores. Polypharmacy was unavoidable in ICU. However, single centre, small sample size, short duration, descriptive design limits its generalizability.